2017
DOI: 10.2196/cancer.6680
|View full text |Cite
|
Sign up to set email alerts
|

Parent and Health Care Provider Perceptions for Development of a Web-Based Weight Management Program for Survivors of Pediatric Acute Lymphoblastic Leukemia: A Mixed Methods Study

Abstract: BackgroundSurvivors of pediatric acute lymphoblastic leukemia (ALL) may experience unhealthy weight gain during treatment, which has been associated with higher risk for chronic health issues.ObjectiveThe purpose of this study was to obtain feedback on weight management in pediatric ALL survivors and on the content and implementation of a Web-based weight management program.MethodsStudy participants included 54 parent survey respondents and 19 pediatric oncology professionals in 4 focus groups. Survey question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The initial curriculum was developed based on the “4-Health” program, a childhood obesity prevention program in rural settings by the US Department of Agriculture (USDA) [26]. The adaption of the curriculum was directly informed by qualitative research that identified targeted nutrition and physical activity needs and specific barriers for childhood ALL survivors [27]. Grounded in theoretical models (e.g., social cognitive and self-determination theories) [28,29], the intervention sessions incorporated core behavioral change strategies including increasing knowledge, setting behavior goals, self-monitoring, problem solving, and positive reinforcement [30].…”
Section: Methodsmentioning
confidence: 99%
“…The initial curriculum was developed based on the “4-Health” program, a childhood obesity prevention program in rural settings by the US Department of Agriculture (USDA) [26]. The adaption of the curriculum was directly informed by qualitative research that identified targeted nutrition and physical activity needs and specific barriers for childhood ALL survivors [27]. Grounded in theoretical models (e.g., social cognitive and self-determination theories) [28,29], the intervention sessions incorporated core behavioral change strategies including increasing knowledge, setting behavior goals, self-monitoring, problem solving, and positive reinforcement [30].…”
Section: Methodsmentioning
confidence: 99%
“…To understand the feasibility of initiating lifestyle interventions early in cancer care, we conducted a mixed-methods study, including 4 focus groups with 20 health care providers (e.g., oncology dietitians, nurses, oncologists and social workers) and surveyed 46 parents of childhood ALL survivors (mean age = 6.5 years old, 61% on-treatment) to evaluate their perceptions of weight management in childhood ALL survivors. 46 About 76% of the parents indicated that they would like to help their child maintain a healthy weight and the most preferred time (47%) to participate in lifestyle interventions was within 3 months after starting maintenance chemotherapy. Health care providers also considered the maintenance phase an appropriate time to introduce lifestyle modification largely because the treatment is less intense and the patients’ family has had time to adapt to the diagnosis of childhood cancer.…”
Section: Early Lifestyle Interventions In Childhood Cancer Survivorsmentioning
confidence: 99%
“…It has been proposed that the emotional impact of childhood cancer diagnosis and the acute treatment phase have been identified as barriers to implementing such an early intervention [ 30 , 64 , 65 ]. Accordingly, in our study, the worsening of the medical condition was one of the main reasons for exclusion from the intervention.…”
Section: Discussionmentioning
confidence: 99%